Comparative epigenomics to clinical trials in human breast cancer and canine mammary tumor - Su-Jin Jeong; Kang-Hoon Lee; Je-Yoel Cho (Animal Cells and Systems)
Epigenetics and epigenomics are captivating fields of molecular biology, dedicated to the exploration of heritable alterations in gene expression and cellular phenotypes, which transpire devoid of any discernible modifications to the fundamental DNA sequence. This intricate regulatory apparatus encompasses multiple mechanisms, prominently featuring DNA methylation, histone modifications, and the involvement of non-coding RNA molecules in pivotal roles. To achieve a comprehensive grasp of these diverse mechanisms, it is imperative to conduct research employing animal models as proxies for human studies. Since experimental animal models like mice and rats struggle to replicate the diverse environmental conditions experienced by humans, this review focuses on comparing common epigenetic alterations in naturally occurring tumors in canine models, which share the human environment, with those in humans. Through this, we emphasize the importance of an epigenetic regulation in the comparative medical approach to a deeper understanding of cancers and further development of cancer treatments. Additionally, we elucidate epigenetic modifications pertinent to specific developmental stages, the ageing process, and the progression of various diseases.